'Nuestro Green New Deal': the Ecosocial Pact of the South and the emergence of biocentric green transitions. - Pantilimon, Ioana (Third World Quarterly, 2023)
This paper deals with the vocabulary of sustainability born in the struggles against extractivism in Latin America and the Caribbean, by focussing on the Pacto Ecosocial e Intercultural del Sur/Ecosocial and Intercultural Pact of the South – an initiative launched in 2020 by a group of critical scholars and activists. In the era of Green New Deals, the Pact calls for a socially conscious green transition benefiting the many. The article shows that the Pact is a counter-hegemonic proposal with a strong biocentric component.